El desarrollo de la Constitución social - Ruiz Rico, Gerardo (Revista de Derecho Político, 2017)
Resumen: La Constitución Española de 1978 reconoce un amplio catálogo de derechos sociales, pero no ha previsto instrumentos eficaces para su tutela jurídica. Los derechos sociales constitucionalizados se configuran ante todo en forma de principios y mandatos dirigidos a los poderes públicos, con escasas posibilidades de ser utilizados en el control de constitucionalidad de las normas. La crisis económica y la constitucionalización del principio de estabilidad presupuestaria han venido a debilitar más aún su potencialidad normativa. La implantación del Estado Autonómico ha tenido como resultado una elevada dosis de descentralización en materia de derechos sociales. Se hace necesaria una reforma constitucional que permita reforzar la eficacia de los derechos del Estado social. Summary: 1. Deficits and normative potentialities of social rights in the Spanish Constitution of 1978. 2. An approximation to the faltering constitutional jurisprudence on social rights and their relative normative capacity. 3. Budgetary stability and economic crisis: new canons of constitutionality of social rights in legislation and constitutional jurisprudence. 4. The territorial development of the Social Constitution. 5. Conclusions: the Social state in a future Constitutione ferenda. Abstract: The Spanish Constitution of 1978 recognizes a wide catalog of social rights, but has not provided effective instruments for its legal protection. Constitutionalised social rights are shaped above all in the form of principles and mandates directed to public authorities, with little possibility of being used in the control of the constitutionality of norms. The economic crisis and the constitutionalisation of the principle of budgetary stability have further weakened its normative potentiality. The implementation of the Autonomous State has resulted in a high dose of decentralization in terms of social rights. A constitutional reform is necessary to strengthen the effectiveness of the rights of the Welfare state.